Keystone microalgae species determine the removal efficiency of sulfamethoxazole: a case study of Chlorella pyrenoidosa and microalgae consortia - Huang, Ruohan; Liu, Wan; Su, Jinghua; Li, Shihao; Wang, Liqing; Jeppesen, Erik; Zhang, Wei (Frontiers in Plant Science, 2023)
In recent years, antibiotics pollution has increased, and microalgae mediated degradation of antibiotics has attracted increasing attention. However, the potential toxicity of antibiotics to keystone microalgae species and their microalgae consortia, and the impact of microalgal diversity on antibiotic removal need to be further studied. In this study, we investigated the removal efficiency and tolerance of five freshwater microalgae (Chlorella pyrenoidosa, Scenedesmus quadricauda, Dictyosphaerium sp., Haematoccocus pluvialis and Botryococcus braunii) and microalgae consortia to sulfamethoxazole (SMX). We found that the removal efficiency of SMX by C. pyrenoidosa reached 49%, while it for the other four microalgae ranged between 9% and 16%. In addition, C. pyrenoidosa, S. quadricauda and Dictyosphaerium sp. had better tolerance to SMX than H. pluvialis, and their growth and photosynthesis were less affected. At 10 and 50 mg/L SMX, the removal capacity of SMX by mixed microalgae consortia was lower than that of C. pyrenoidos except for the consortium with C. pyrenoidos and S. quadricauda. The consortia generally showed higher sensitivity towards SMX than the individual species, and the biochemical characteristics (photosynthetic pigment, chlorophyll fluorescence parameters, superoxide anion (O2-), superoxide dismutase activity (SOD), malondialdehyde (MDA) and extracellular enzymes) were significantly influenced by SMX stress. Therefore, the removal of antibiotics by microalgae consortia did not increase with the number of microalgae species. Our study provides a new perspective for selection of microalgal consortia to degrade antibiotics.